Whole-genome resequencing reveals Brassica napus origin and genetic loci involved in its improvement - Lu, Kun; Wei, Lijuan; Li, Xiaolong; Wang, Yuntong; Wu, Jian; Liu, Miao; Zhang, Chao; Chen, Zhiyou; Xiao, Zhongchun; Jian, Hongju; Cheng, Feng; Zhang, Kai; et al. (Nature communications, 2019)
Brassica napus (2 n = 4 x = 38, AACC) is an important allopolyploid crop derived from interspecific crosses between Brassica rapa (2 n = 2 x = 20, AA) and Brassica oleracea (2 n = 2 x = 18, CC). However, no truly wild B. napus populations are known; its origin and improvement processes remain unclear. Here, we resequence 588 B. napus accessions. We uncover that the A subgenome may evolve from the ancestor of European turnip and the C subgenome may evolve from the common ancestor of kohlrabi, cauliflower, broccoli, and Chinese kale. Additionally, winter oilseed may be the original form of B. napus . Subgenome-specific selection of defense-response genes has contributed to environmental adaptation after formation of the species, whereas asymmetrical subgenomic selection has led to ecotype change. By integrating genome-wide association studies, selection signals, and transcriptome analyses, we identify genes associated with improved stress tolerance, oil content, seed quality, and ecotype improvement. They are candidates for further functional characterization and genetic improvement of B. napus . Brassica napus is a globally important oil crop, but the origin of the allotetraploid genome and its improvement process are largely unknown. Here, the authors take a population genetic approach to resolve its origin and evolutionary history, and identify candidate genes related to important agricultural traits.